1963
DOI: 10.1080/00288233.1963.10418135
|View full text |Cite
|
Sign up to set email alerts
|

The biology and control ofColeophoraspp. (Lepidoptera-Coleophoridae) on white clover

Abstract: The overwintering larvae of Coleophora spissicornis Howarth and C. alcyonipennella Kollar are in diapause during 1 winter only, and pupate in the following spring. It is concluded that in general the larval progeny of the first-brood moths do most of the damage to seed crops. C. alcyonipennella, which is usually numerically dominant in the first brood flight period, is the more injurious of the 2 species. In a field test at equivalent dosages both DDT and toxaphene gave good immediate control of the moths pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1966
1966
1983
1983

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…This confirms Dumbleton's (1963) observations. However, in contrast to Dumbleton, I have found C. spissicornis~o be the numerically superior species and since the seed consumption of their larvae is about equal to that of C. jrischella I consider this species to be the more damaging.…”
Section: Resultssupporting
confidence: 81%
“…This confirms Dumbleton's (1963) observations. However, in contrast to Dumbleton, I have found C. spissicornis~o be the numerically superior species and since the seed consumption of their larvae is about equal to that of C. jrischella I consider this species to be the more damaging.…”
Section: Resultssupporting
confidence: 81%
“…(2) (288) Larvae collected mid-winter and maintained in the laboratory at 22 k 1 '-C removed the silken webbing from both ends of their cases and crawled around their petri dishes in late August-September. Similar "spring movement" (Dumbleton 1963), was observed in the field in October-November.…”
Section: Resultssupporting
confidence: 74%
“…This paper outlines field and laboratory observations made in Tasmania on the biology and behaviour of C. frischella from 1965 to 1972 and contrasts them to observations made in New Zealand by Dumbleton (1952Dumbleton ( , 1963, Stuart (1958) and Pearson (1975), especially.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…in white clover seed crops. The most satisfactory control of this pest has been achieved by the application of insecticide sprays to the crop when in full flower (Dumbleton 1963) and therefore at the stage most attractive to honey bees. Field tests have shown that many of the materials that have shown promise for the control of the pest were too toxic to honey tees to make further work with them worth while.…”
Section: Introductionmentioning
confidence: 99%